Etika Politik Dalam Pandangan Machievelli dan Al Mawardi - Iqbal Maulana Alfiansyah; Sofi Mubarok; Yulia Rimapradesi; Nabila Yasmin Namira; Ida Susilowati (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2023)
Ethics is usually closely related to the values and norms that exist in a society. In practice, political ethics demands that all claims to the right to organize association be accounted for on basic moral principles. Therefore political ethics seeks to help society to realize the noble state ideology into objective political reality. This study discusses the Machievelli’s view of political ethics and its comparison with the Islamic theory of political ethics. Previous research focused more on understanding political ethics according to Machievelli only and understanding political ethics according to Islam only. While this research will complement the last gap research, namely comparing the understanding of political ethics according to Machievelli and Islam. The authors used a descriptive method with data collection techniques in journals, articles, and other literature in this study. From the perspective of Machievelli, ethics is often considered secondary or not essential. Political ethics cannot be applied in international politics and prioritizes self-interest rather than moral principles. Realizing self-interest by the state is seen as a right, or a duty considered a realist principle. In contrast, Islam views political ethics as a guide that upholds the values of justice and respects human rights to create sustainable peace under religious norms.Keywords: Political Ethics, Machievelli, Al MawardiAbstrakEtika biasanya berhubungan erat dengan nilai dan norma yang ada dalam suatu masyarakat. Dalam praktiknya, etika politik menuntut agar segala klaim atas hak untuk menata masyarakat dipertanggungjawabkan pada prinsip-prinsip moral dasar. Maka dari itu etika politik berusaha membantu masyarakat untuk mewujudkan ideologi negara yang luhur ke dalam realitas politik yang nyata. Penelitian ini membahas tentang pandangan Machievelli terhadap etika politik dan perbandingannya dengan pandangan Islam terhadap etika politik. Dalam penelitian sebelumnya, penelitian lebih terfokus pada pemahaman etika politik menurut Machievelli saja dan pemahaman etika politik menurut Al Mawardi saja. Sedangkan penelitian ini akan melengkapi Gap penelitian sebelumnya, yaitu membandingkan pemahaman etika politik menurut Machievelli dan Al Mawardi. Dalam penelitian ini, penulis menggunakan metode deskriptif dengan teknik pengumpulan data berupa jurnal- jurnal, artikel-artikel, dan literatur lainnya. Menurut Machievelli, etika adalah hal yang seringkali dianggap sekunder atau tidak pokok. Etika politik tidak dapat diterapkan dalam politik internasional dan mengutamakan kepentingan diri daripada prinsip moral. Mewujudkan kepentingan diri oleh negara dipandang sebagai sebuah hak, atau tugas yang dianggap menjadi prinsip kaum realis. Sementara, Islam memandang bahwa etika politik merupakan prinsip yang menjunjung tinggi nilai-nilai keadilan dan menghormati hak asasi manusia, sehingga tercipta suatu kedamaian yang berkelanjutan dibawah norma-norma agama.Kata Kunci: Etika Politik, Machievelli, Al Mawardi